ANALISIS NOVEL SAMAN KARYA AYU UTAMI: TINJAUAN SOSIOLOGI SASTRA - Titin Aisyah; Restu Wahyuni; Wikanengsih Wikanengsih (IKIP Siliwangi, 2019)
This research is motivated by at least a literaly work that discusses a position of woman in society in culture and marriage bond. The focus of research refers to relation of novel with author, novel with society and social purpose novel in society. The method that used in this research is drescriptive qualitative with the data source from Saman novel by Ayu Utami and some kind of relevant research. The result of reserch show that complexity of issues that presented in Saman accurate with data about social events in Indonesia.Through Saman, Ayu expressed her thoughts about religion, sex, marriage, race, economics, and politics. Besides, space, time, and event that used as reference contextual in Saman can't be separated from social and politics that causes it.At least, saman telling about process of land takeover, nepotism, abduction, social inequality, representing new order era that shows the attitude and the responses of the characters in the face of the problem.